The Afroscope Podcast - Association of Evangelicals in Africa
The podcast will allow evangelical leaders across the continent to engage in conversations that will seek to address the intricate issues facing the church in Africa. It will be a platform to mobilize the reached church in Africa to missions into unreached Africa. It will seek to provide an avenue for capacity building of the National Evangelical Alliances and partner organizations who are working with the church to ensure both the proclamation and the demonstration of the gospel.
free